2019
DOI: 10.3389/fpubh.2019.00273
|View full text |Cite
|
Sign up to set email alerts
|

Together for Health: An Initiative to Access Health Services for the Hispanic/Mexican Population Living in the United States

Abstract: A disproportionately small percentage of the Hispanic/Mexican population in the United States has adequate access to health services, which decreases quality of life at both the individual and community levels. In addition, it increases risk for preventable diseases through insufficient screening and management. The Mexican Section of the U.S./Mexico Border Health Commission, in efforts to address barriers to accessing preventive health care services for vulnerable populations, launched the initiative Juntos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Outreach and technology-based approaches, including home visit programs, 43 mobile health units, 44 and telemedicine, 45 may be particularly important in bridging the GHA gaps for this and other largely rural populations in the southeastern United States. Various studies have shown that telemedicine has great, largely unfulfilled, potential to facilitate healthcare access among Latinos/as/x in rural areas 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Outreach and technology-based approaches, including home visit programs, 43 mobile health units, 44 and telemedicine, 45 may be particularly important in bridging the GHA gaps for this and other largely rural populations in the southeastern United States. Various studies have shown that telemedicine has great, largely unfulfilled, potential to facilitate healthcare access among Latinos/as/x in rural areas 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The MHU staff provided credible health information regarding COVID-19, emotional support, and serve as a link to community resources during a difficult time. The method was later synchronized and used by the Mexican Section of the U.S.-Mexico Border Health Commission across all 11 mobile health units ( 21 ) and 50 Ventanillas de Salud (VDS) and (Health Windows (HW) inside Mexico's Consular Network across the United States ( 22 ). Due to the high-need responses during the call-back campaign, the MHU staff provided mobile unit users with a paper version of the “COVID-19 call-back survey.” The MOVE-UP project was later created to help increase COVID-19 vaccination rates in Arizona with an emphasis among vulnerable populations.…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, los inmigrantes mexicanos son la población con menor probabilidad de tener uno, y los indocumentados tienen el doble de posibilidades de no tener seguro médico en comparación con los migrantes documentados. lo que los sitúa en mayor vulnerabilidad, al tener que regresar a su país de origen o vivir en enfermedad tanto física como emocional 7 , lo cual, agrava la situación en la cual se encuentran. Entre las posibles soluciones algunos autores proponen una reforma a las leyes de migración 8 , con lo cual concordamos; así como siempre buscar la alternativa legal para una inmigración segura.…”
Section: Desarrollounclassified